(untitled) (Scientific journal of the Fergana State University, 2025)
The study devoted to the assessment of ecotoxicological and geomorphological state of the Yuntolovsky Sanctuary soils was aimed at studying the effectiveness of protected areas organization within the boundaries of such large urban agglomerations as St. Petersburg. The negative impact of anthropogenic activities on soils of various terrestrial ecosystems of the study area was shown.